Bionic women and men ‐ Part 1: Cardiovascular lessons from heart failure patients implanted with left ventricular assist devices. Issue 5 (3rd April 2020) - Stöhr, Eric J.; Cornwell, William K.; Kanwar, Manreet; Cockcroft, John R.; McDonnell, Barry J.
Abstract : New Findings: What is the topic of this review? Patients with advanced heart failure who are implanted with left ventricular assist devices (LVADs) present an opportunity to understand the human circulation under extreme conditions. What advances does it highlight? LVAD patients have a unique circulation that is characterized by a reduced or even absent arterial pulse. The remarkable survival of these patients is accompanied by circulatory complications, including stroke, gastrointestinal bleeding and right‐heart failure. Understanding the mechanisms related to the complications in LVAD patients will help the patients and also advance our fundamental understanding of the human circulation in general. Abstract: Some humans with chronic, advanced heart failure are surgically implanted with a left ventricular assist device (LVAD). Because the LVAD produces a continuous flow, a palpable pulse is often absent in these patients. This allows for a unique investigation of the human circulation and has created a controversy around the 'need' for a pulse. The medical debate has also generated a more generic, fundamental discussion into what is 'normal' arterial physiology and health. The comprehensive study and understanding of the arterial responses to drastically altered haemodynamics due to continuous‐flow LVADs, at rest and during activity, presents an opportunity to significantly increase our current understanding of the fundamental components of arterial regulation (flow, blood pressure, sympathetic activity, endothelial function, pulsatility) in a way that could never have been studied previously. In a series of four articles, we summarize the talks presented at the symposium entitled 'Bionic women and men – Physiology lessons from implantable cardiac devices' presented at the 2019 Annual Meeting of The Physiological Society in Aberdeen, UK. The articles highlight the novel questions generated by physiological phenomena observed in LVAD patients and propose future areas of interest within the field of cardiovascular physiology. Abstract :